Peeled two-dimensional molybdenum disulfide nanosheet modified lithium negative electrode as well as preparation method and application thereof
By using peeled two-dimensional molybdenum disulfide nanosheets to modify the lithium negative electrode in lithium sulfur batteries, the problems of lithium dendrites growth and polysulfide shuttle effects are solved, and the uniform deposition of lithium ions and the improvement of battery safety is achieved, and the system is extended. The battery life and energy density are improved.
Patent Information
- Application Number
- CN202411296496.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-01-03
AI Technical Summary
The prior art is difficult to simultaneously regulate the positive and negative electrodes of lithium sulfur batteries, resulting in uncontrollable growth of lithium dendrites and serious polysulfide shuttle effect, hindering the progress of practicalization of lithium sulfur batteries.
The lithium negative electrode is modified by peeled two-dimensional molybdenum disulfide nanosheets. The colloidal molybdenum disulfide dispersion is formed by mixing the molybdenum disulfide powder with n-butyl lithium solution, filtering and sonication, and a load composite is formed on the polypropylene separator. The film is transferred to the surface of metal lithium by rolling pressing technology to form a peeled molybdenum disulfide nanosheet modified lithium negative electrode to achieve uniform deposition of lithium ions and barriers to polysulfide migration.
Effectively inhibit the growth of lithium dendrites, promote the adsorption and conversion of polysulfides, improve the efficiency of electrochemical reactions, enhance battery safety and cycle life, and reduce the nucleation overpotential of the negative electrode lithium ions, realize the uniform deposition and reversible peeling of lithium ions, and improve the The energy density and safety of lithium-sulfur batteries.
Smart Images

Figure CN119252871A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of a new generation of high-performance green energy storage, and specifically relates to a lithium negative electrode diaphragm and a preparation method and application thereof, and more specifically relates to a lithium negative electrode modified with an exfoliated two-dimensional molybdenum disulfide nanosheet and a preparation method and application thereof. Background Art
[0002] With the large-scale application of mobile electronic devices and electric vehicles and the rapid development of smart grid technology, large-scale energy storage technology will play an important role in the development of power systems and energy transformation. Future electric vehicles require batteries with higher mileage, faster charging speeds and longer life. Lithium-sulfur batteries have high theoretical discharge capacity and high energy density, making them one of the ideal next-generation energy storage systems. However, the polysulfide shuttle effect in the sulfur positive electrode and the uncontrollable growth of lithium dendrites on the lithium metal negative electrode have severely restricted the practical application of lithium-sulfur batteries.
[0003] At present, due to the poor compatibility of most materials, the solution to key problems in lithium-sulfur batteries is often isolated, and it is difficult to achieve bidirectional regulation of positive and negative electrodes simultaneously. The modification of lithium metal negative electrodes mainly focuses on the design of artificial electrode electrolyte interface (SEI) and lithium-philic skeleton, but both aspects are difficult to achieve large-scale production, which greatly restricts the practicality of lithium metal batteries. It is worth noting that in lithium metal battery systems, because they involve multi-electron reaction paths, the diaphragm can not only avoid short circuits between positive and negative electrodes and maintain ion channels between positive and negative electrodes, but also play a greater role through multifunctionality. Therefore, researchers have also made a lot of innovative work on the diaphragms used in lithium metal batteries. For example, Advanced Energy Materials (Advanced Energy Materials.2018, 8, 1802130) reported a MOF@PVDF-HFP battery diaphragm prepared with HKUST-1 nanoparticles as assembly units and poly (vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) as a binder. The highly uniform pore size of MOF particles completely suppresses the shuttle effect. However, the thickness and surface density of this diaphragm are much greater than those of ordinary diaphragms, and the non-conductive MOF makes it difficult to alleviate the slow dynamics on the positive electrode side. These factors seriously restrict the energy density of lithium-sulfur batteries.
[0004] The prior art discloses modifying the separator between the positive and negative electrodes. Although it can inhibit the shuttling effect of polysulfides, the uncontrollable growth of lithium dendrites on the lithium metal negative electrode cannot be effectively controlled. Therefore, it is difficult to achieve bidirectional regulation of the positive and negative electrodes simultaneously. Therefore, so far, there has been no report on a strategy that can achieve low-cost, simple and fast regulation of the positive and negative electrodes of lithium-sulfur batteries. This situation has greatly hindered the practical progress of the new generation of lithium-sulfur battery energy storage systems. Summary of the invention
[0005] In response to the need for improvement in the prior art, the present invention provides a lithium negative electrode modified with an exfoliated two-dimensional molybdenum disulfide nanosheet, and a preparation method and application thereof, the purpose of which is to solve the problem of lithium dendrite growth at the negative electrode and the polysulfide shuttling effect in lithium-sulfur batteries. The exfoliated two-dimensional molybdenum disulfide nanosheet can regulate the uniform deposition of lithium ions and stabilize the electrode electrolyte interface. At the same time, the molybdenum disulfide nanosheet can effectively block the migration of polysulfides to the negative electrode, enhance the chemical adsorption and recycling capacity of active substances, and greatly improve the safety and cycle life of lithium-sulfur batteries.
[0006] According to a first aspect of the present invention, a method for preparing a lithium negative electrode modified with an exfoliated two-dimensional molybdenum disulfide nanosheet is provided, characterized in that it comprises the following steps:
[0007] (1) adding molybdenum disulfide powder to n-butyl lithium solution, mixing and filtering, retaining the supernatant, and adding a polar solvent to the supernatant to form colloidal molybdenum disulfide;
[0008] (2) adding colloidal molybdenum disulfide to water, obtaining an exfoliated molybdenum disulfide (EMoS2) dispersion after ultrasonic treatment, diluting the dispersion with ethanol or deionized water, and then filtering it on a polypropylene membrane to form an exfoliated molybdenum disulfide-loaded polypropylene composite membrane (EMoS2@PP);
[0009] (3) After drying the composite film obtained in step (2), the side containing the exfoliated molybdenum disulfide is adhered to metallic lithium, and the exfoliated molybdenum disulfide is transferred to the surface of metallic lithium by rolling technology, and then the polypropylene is removed to obtain a lithium negative electrode modified with exfoliated molybdenum disulfide nanosheets (EMoS2@Li).
[0010] Preferably, in step (1), the polar solvent is one or more of n-hexane, diethyl ether, tetrahydrofuran, dimethylsulfamide and cyclohexane.
[0011] Preferably, the mass volume ratio of the molybdenum disulfide powder to the n-butyl lithium solution in step (1) is 50 to 200 mg / ml.
[0012] Preferably, in step (1), mixing is carried out by stirring, the stirring time is 24 to 36 hours, and the stirring temperature is 40 to 60°C.
[0013] Preferably, in step (2), the ultrasonication time is 1 to 3 hours.
[0014] Preferably, the drying in step (3) is first drying in air for 6 to 8 hours and then vacuum drying for 6 to 8 hours.
[0015] According to another aspect of the present invention, a lithium negative electrode prepared by a method for preparing a lithium negative electrode modified with an exfoliated two-dimensional molybdenum disulfide nanosheet is provided.
[0016] According to another aspect of the present invention, a lithium-sulfur battery is provided, comprising a carbon-sulfur positive electrode, the lithium negative electrode (EMoS2@Li), an intermediate separator, and an electrolyte.
[0017] Preferably, the preparation method of the intermediate diaphragm is as follows: (1) adding molybdenum disulfide powder to n-butyl lithium solution, filtering after mixing, retaining the supernatant, and adding a polar solvent to the supernatant to form colloidal molybdenum disulfide; (2) adding colloidal molybdenum disulfide to water, obtaining an exfoliated molybdenum disulfide dispersion after ultrasound, diluting the dispersion with ethanol or deionized water, and then filtering on a polypropylene diaphragm to form an exfoliated molybdenum disulfide-loaded polypropylene composite membrane (EMoS2@PP).
[0018] According to another aspect of the present invention, there is provided an application of the lithium negative electrode, wherein the lithium negative electrode is used as the negative electrode of a lithium-sulfur battery.
[0019] In general, the above technical solution conceived by the present invention has the following technical advantages compared with the prior art:
[0020] (1) The EMoS2 nanosheet material of the present invention exhibits a uniform, continuous and flat two-dimensional layered structure, has excellent electrocatalytic effect, can accelerate the adsorption and conversion of polysulfides, and keep the polysulfides at the positive electrode; secondly, EMoS2 has good electrical conductivity, can promote electron transfer, and help the electrochemical reaction, thereby helping to prevent the migration of polysulfides to the negative electrode. In addition, the EMoS2 nanosheet can effectively reduce the nucleation overpotential of lithium ions at the negative electrode, thereby promoting their uniform deposition and inhibiting the growth of potential dendrites to the positive electrode.
[0021] (2) The EMoS2 nanoparticles of the present invention contain rich 1T metal phases and vacancy structures. As EMoS2@Li, they can effectively regulate the deposition of lithium ions on the negative electrode side, inhibit the growth of lithium dendrites and side reactions such as lithium precipitation, reduce safety hazards such as thermal runaway, and improve the safety and cycle life of lithium-sulfur batteries; as the intermediate separator EMoS2@PP, the two-dimensional molybdenum disulfide sheet structure can effectively block the migration of polysulfides to the negative electrode, enhance the chemical adsorption and recycling capabilities of active substances, and greatly improve the cycle life of lithium-sulfur batteries. The present invention creatively loads EMoS2 nanosheets on the lithium negative electrode (EMoS2@Li) to modify the negative electrode, inhibit the generation of lithium dendrites, and achieve uniform deposition and reversible stripping of lithium ions.
[0022] (3) The EMoS2 nanosheets obtained by the method of the present invention are thin and light in weight. Compared with the traditional carbon layer, they do not increase the thickness and weight of the separator and the lithium negative electrode, which is beneficial to improving the energy density of the entire battery system.
[0023] (4) The EMoS2 produced by the present invention has a high yield, a short time cycle, can be produced continuously, and has a simple process and strong compatibility. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is an optical picture of the EMoS2 ethanol dispersion prepared in Example 1;
[0025] Figure 2 A high-resolution transmission electron microscope (TEM) of the EMoS2 prepared in Example 1;
[0026] Figure 3 TEM of EMoS2 prepared in Example 1 ( Figure 2 )'s element mapping map;
[0027] Figure 4 Atomic force microscopy (AFM) image of EMoS2 prepared in Example 1;
[0028] Figure 5 The electron paramagnetic resonance (EPR) spectrum of EMoS2 prepared in Example 1;
[0029] Figure 6 X-ray diffraction (XRD) of EMoS2 and pristine MoS2 prepared in Example 1;
[0030] Figure 7 Optical photograph of EMoS2@PP prepared in Example 1;
[0031] Figure 8 This is a scanning electron microscope (SEM) photograph of EMoS2@PP prepared in Example 1;
[0032] Fig. 9 Mo 3d X-ray photoelectron spectrum (XPS) of EMoS2@PP prepared in Example 1
[0033] Fig.10 The EMoS2@PP prepared in Comparative Example 1 has a sulfur loading of 1.2 mg cm -2 Cycle diagram of time.
[0034] Fig.11 The EMoS2@Li negative electrode prepared in Example 2 matches the EMoS2@PP separator at a sulfur loading of 1.2 mg cm -2 Cycle diagram of time. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0036] Example 1
[0037] This embodiment provides a lithium negative electrode modified by exfoliation of molybdenum disulfide (EMoS2@Li), and the preparation method thereof is as follows:
[0038] (1) First, add 5 ml of n-butyl lithium in n-hexane to a reagent bottle containing 500 mg of commercial MoS2 (BMoS2) powder. Place the solution in a glove box and stir it at room temperature in an argon environment for 24 hours. After filtering, retain the supernatant and wash the supernatant with n-hexane several times to remove residual n-butyl lithium. Then, quickly immerse the colloidal MoS2 solution in deionized water and ultrasonicate for 1 hour to obtain EMoS2.
[0039] (2) The EMoS2 solution was first diluted with anhydrous ethanol and then dispersed in anhydrous ethanol to form a uniform solution. Subsequently, the EMoS2 was coated on a commercial PP separator by vacuum filtration to form EMoS2@PP.
[0040] (3) The side of EMoS2@PP containing EMoS2 is laminated onto metallic lithium, and EMoS2 is transferred to the surface of metallic lithium using a roller pressing technique, thereby obtaining EMoS2@Li.
[0041] Figure 1 is an optical photograph of the EMoS2 ethanol solution. From the optical photograph, it can be seen that the EMoS2 ethanol solution has uniform color and no particles agglomerate; Figure 2 This is the high-resolution TEM of the prepared EMoS2, which shows that the nanosheets contain a large amount of 1T phase; Figure 3 This is the mapping map of the prepared EMoS2, which shows the good distribution of elemental sulfur and molybdenum; Figure 4 The AFM spectrum of the prepared EMoS2 shows that the thickness of the peeled nanosheets is 1.46-2.36 nm; Figure 5 This is the electron paramagnetic resonance spectrum of the prepared EMoS2, indicating that the EMoS2 nanosheets contain obvious defect sites; Figure 6Figure 2 shows the XRD patterns of the prepared MoS2 and EMoS2. Compared with MoS2, EMoS2 has only one broad diffraction peak located at 2θ=14.42°, indicating that the exfoliated MoS2 nanosheets only retain the (002) peak. The absence of other peaks and the width of the (002) peak indicate that the nanosheets are randomly arranged during the stacking process, with large spacing between layers. Figure 7 This is an optical photograph of the prepared EMoS2@PP, which has a bright color, indicating the metallic properties of EMoS2 nanosheets; Figure 8 This is the SEM image of the prepared EMoS2@PP, which shows that it has dense, smooth and continuous nanosheets; Fig. 9 The X-ray photoelectron spectrum (XPS) of the prepared EMoS2@PP shows that the high-conductivity 1T phase accounts for 70%;
[0042] Example 2
[0043] In order to verify the effect of EMoS2@Li prepared in Example 1 of the present invention, carbon nanotubes / sulfur were used as the positive electrode material, EMoS2@Li was used as the negative electrode, and EMoS2@PP was used as the middle separator to assemble a 2032-type button cell. -1 Lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) as lithium salt and 2wt% LiNO3 as additive were added to 1,2-dimethoxyethane (DME) / 1,3-dioxolane (DOL) (volume ratio = 1:1) as electrolyte, and the battery's charge and discharge voltage range was 1.7 to 2.8 V. Cyclic performance tests were conducted on a Xinwei charge and discharge instrument at a test temperature of 25°C.
[0044] Preparation of carbon nanotube / sulfur as positive electrode: 200 mg carbon nanotube and 800 mg sulfur were ground evenly, then placed in a round-bottom flask and sealed at 155 °C for 10 hours, and then carbon nanotube / sulfur, lithiated polyacrylic acid binder (LA133) and conductive agent Ketjen black composite slurry were prepared in a ratio of 9:0.5:0.5, stirred in a certain amount of deionized water for 10 hours, coated on aluminum foil, and dried at 65 °C for 12 hours. The surface sulfur loading of the positive electrode was controlled to be 1-2 mg cm -2 , use the above-mentioned electrode as the positive electrode.
[0045] Fig.11 The long cycle performance diagram of the EMoS2@Li negative electrode prepared in Example 2 matched with the EMoS2@PP intermediate membrane battery shows that under the combined effect of the EMoS2@Li and EMoS2@PP membranes, the initial discharge capacity of the lithium-sulfur battery is 866.2 mAhg -1 After 680 cycles, it still has 710 mAh g -1The high capacity retention and capacity decay rate of 0.026% indicate that the EMoS2 on the surface of the lithium negative electrode has higher ionic conductivity and better lithium affinity, which greatly inhibits the growth of lithium dendrites and realizes the uniform deposition and reversible stripping of lithium ions, thereby improving the cycle stability of the battery, reducing the capacity decay rate, and thus extending the life of the battery.
[0046] Comparative Example 1
[0047] Carbon nanotubes / sulfur are used as the positive electrode material, EMoS2@PP is used as the middle separator, and lithium is used as the negative electrode to assemble a 2032-type button cell. -1 Lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) as lithium salt and 2wt% LiNO3 as additive added to 1,2-dimethoxyethane (DME) / 1,3-dioxolane (DOL) (volume ratio = 1:1) as electrolyte, the battery charge and discharge voltage range is 1.7~2.8V. Cyclic performance test was carried out on the Xinwei charge and discharge instrument, and the test temperature was 25.℃
[0048] Preparation of carbon nanotube / sulfur as positive electrode: 200 mg carbon nanotube and 800 mg sulfur were ground evenly, then placed in a round-bottom flask and sealed at 155 °C for 10 hours, and then carbon nanotube / sulfur, lithiated polyacrylic acid binder LA133 and conductive agent Ketjen black composite slurry were prepared in a ratio of 9:0.5:0.5, stirred in a certain amount of deionized water for 10 hours, coated on aluminum foil, and dried at 65 °C for 12 hours. The surface sulfur loading of the positive electrode was controlled to be 1-2 mg cm -2 , use the above-mentioned electrode as the positive electrode.
[0049] Fig.10 The cycle diagram of EMoS2@PP prepared in comparative example 1 matching carbon nanotube / sulfur cathode shows that EMoS2@PP can make carbon nanotube / sulfur cathode at 1.2 mg cm -2 The cycling capacity after 600 stable cycles at a loading of 1.547 W was 602.7 mAh g -1 , the capacity decay rate is 0.067%.
[0050] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a lithium negative electrode modified by an exfoliated two-dimensional molybdenum disulfide nanosheet, characterized in that: The following steps are involved: (1) adding molybdenum disulfide powder to n-butyl lithium solution, mixing and filtering, retaining the supernatant, and adding a polar solvent to the supernatant to form colloidal molybdenum disulfide; (2) adding colloidal molybdenum disulfide to water, obtaining an exfoliated molybdenum disulfide dispersion after ultrasonic treatment, diluting the dispersion with ethanol or deionized water, and then filtering it on a polypropylene membrane to form an exfoliated molybdenum disulfide-loaded polypropylene composite membrane; (3) After drying the composite film obtained in step (2), the side containing the stripped molybdenum disulfide is adhered to metallic lithium, and the stripped molybdenum disulfide is transferred to the surface of the metallic lithium by rolling technology, and then the polypropylene is removed to obtain a lithium negative electrode modified with stripped molybdenum disulfide nanosheets.
2. The method for preparing a lithium negative electrode modified by an exfoliated two-dimensional molybdenum disulfide nanosheet according to claim 1, characterized in that: In step (1), the polar solvent is one or more of n-hexane, diethyl ether, tetrahydrofuran, dimethylsulfamide and cyclohexane.
3. The method for preparing a lithium negative electrode modified by an exfoliated two-dimensional molybdenum disulfide nanosheet according to claim 1, characterized in that: The mass volume ratio of the molybdenum disulfide powder to the n-butyl lithium solution in step (1) is 50-200 mg / ml.
4. The method for preparing a lithium negative electrode modified by an exfoliated two-dimensional molybdenum disulfide nanosheet according to claim 1, characterized in that: In step (1), the mixture is mixed by stirring for 24 to 36 hours at a temperature of 40 to 60°C.
5. The method for preparing a lithium negative electrode modified by an exfoliated two-dimensional molybdenum disulfide nanosheet according to claim 1, characterized in that: In step (2), the ultrasonication time is 1 to 3 hours.
6. The method for preparing a lithium negative electrode modified by an exfoliated two-dimensional molybdenum disulfide nanosheet according to claim 1, characterized in that: The drying in step (3) is first drying in air for 6 to 8 hours and then vacuum drying for 6 to 8 hours.
7. A lithium negative electrode prepared by the method for preparing a lithium negative electrode modified with an exfoliated two-dimensional molybdenum disulfide nanosheet as described in any one of claims 1 to 6.
8. A lithium-sulfur battery, characterized in that: It includes a carbon-sulfur positive electrode, and also includes a lithium negative electrode as described in claim 7, an intermediate separator, and an electrolyte.
9. A lithium-sulfur battery as claimed in claim 8, characterized in that: The preparation method of the intermediate diaphragm is as follows: (1) adding molybdenum disulfide powder to n-butyl lithium solution, mixing and filtering, retaining the supernatant, and adding a polar solvent to the supernatant to form colloidal molybdenum disulfide; (2) adding the colloidal molybdenum disulfide to water, obtaining an exfoliated molybdenum disulfide dispersion after ultrasonic treatment, diluting the dispersion with ethanol or deionized water, and then filtering on a polypropylene diaphragm to form an exfoliated molybdenum disulfide-loaded polypropylene composite membrane.
10. The use of the lithium negative electrode as claimed in claim 7, characterized in that: The lithium negative electrode is used as a negative electrode of a lithium-sulfur battery.